HUBUNGAN TINGKAT KECUKUPAN ENERGI, PROTEIN DAN INDEKS MASSA TUBUH (IMT) DENGAN POWER ATLET BELADIRI - Laila Maulida Hidayah; Lailatul Muniroh (Media Gizi Indonesia, 2017)
Athletes require greater energy and protein than people with normal activity to balance the body’s metabolic rate. The body mass index is a factor which directly related to the physical performance of martial-art athletes. The objective of this study was to analyze the relationship between energy, protein suffi ciency and body mass index with power of martial-art athletes. This research was observational analytic with cross sectional study design. Samples were consisted of 46 athletes who has won at least one martial art games. Data were collected through interview. Energy and protein adequacy level were measured by 2 × 24 hours food recall questionnaires; body weight and height measured by digital scale and microtoice; and power was measured with vertical jump test. There was a positive relationship between adequacy level of protein (p = 0.011) and athletes’s power, but negative correlation between BMI and athlethes’s power (p = 0.019). There was no relationship between the adequacy level of energy with power of martial-art athletes. It was concluded that increament of protein adequacy level could increase athlete’s power. Otherwise, escalation of body mass index could decrease the power of athletes. Therefore, it is needed to monitor nutrient intake and BMI to increase the power of martial-art athletes.